KYRGYZ ETHNOGRAPHIC TERMS IN CONTEMPORARY PUBLIC ADVERTISING - Isakov, Baktybek Baatyrbek (Annals of Spiru Haret University. Economic Series, 2022)
The usage of a variety of stylistic and lexical means makes the language of advertisements colorful, rich, and bright. Language of advertising is been created with an aim to attract customers’ attention and provoke them to the further actions. This paper covers the examples of the advertisements taken from the Kyrgyz language in order to demonstrate the structural traits of the advertising discourse; the analysis of the advertisements in Kyrgyz assists to reveal the main contextual notions represented in advertising. The paper hypothesis is that the advertisements in Kyrgyz can greatly influence the views of ordinary people. The paper has been accompanied by the examples taken from the mass media sources functioning in Kyrgyzstan.